'If a fight starts, watch the crowd': The effect of violence on popular support for social movements. (July 2019) - Muñoz, Jordi; Anduiza, Eva
Social movements often face tactic diversification. In otherwise nonviolent movements, some groups or radical flanks may resort to violent actions such as street rioting. This article analyzes the impact that these violent episodes can have on popular support for the movement as a whole. To estimate the causal effect of violence, it exploits an unexpected riot outbreak that occurred during the fieldwork of a face-to-face survey in Barcelona in May 2016, led by a squat group linked to the anti-austerity movement known as the 15-M or indignados that emerged during the financial crisis. By comparing respondents interviewed before and after the riots, it finds that the street violence episode reduced support for the 15-M movement by 12 percentage points on average. However, the magnitude of the effect is highly conditional on the respondents' predispositions towards the movement. Core supporters, that are expected to share the frame of the movement in justifying violent actions, are the least affected by the violent outbreak. On the other extreme, weak supporters, opposers, and non-aligned citizens reduce their support to a larger extent. Results are robust to different specifications and a wide range of robustness checks. These findings have potentially important implications for movements concerned with broadening their support base.